Conclusions - Verena Balz (A+BE: Architecture and the Built Environment)
To design for the purpose of planning was not new when regional design emerged as a distinguished discipline in the 1980s in the Netherlands. On the contrary, to imagine solutions for particular areas and to discuss these for the purpose of planning has been a long-standing tradition that can be traced back to the emergence of urban planning in the early 20th century. However, when spatial planning emerged as a new, more collaborative and anticipatory planning approach in the last decades, expectations concerning performances of design in planning decision-making increased. Design came to be seen as a practice that not only improves the spatial and technical quality of plans, but also enhances planning innovation, clarifies political agendas, forges societal alliances and raises the efficiency of planning through timely consideration of conflicts that planning may cause in societal and political domains. Since the 1990s, regional design underwent a process of institutionalisation in Dutch national planning. The practice became repetitively used and was formally embedded in planning procedures.